A Review on the Anti-Inflammatory Activity of Pomegranate in the Gastrointestinal Tract. (14th March 2013) - Colombo, Elisa; Sangiovanni, Enrico; Dell'Agli, Mario
Abstract : Several biological activities of pomegranate have been widely described in the literature, but the anti-inflammatory effect in the gastrointestinal tract has not been reviewed till now. The aim of the present paper is to summarize the evidence for or against the efficacy of pomegranate for coping with inflammatory conditions of the gastro-intestinal tract. The paper has been organized in three parts: (1) the first one is devoted to the modifications of pomegranate active compounds in the gastro-intestinal tract; (2) the second one considering the literature regarding the anti-inflammatory effect of pomegranate at gastric level; (3) the third part considers the anti-inflammatory effect of pomegranate in the gut. In vivo studies performed on the whole fruit or juice, peel, and flowers demonstrate antiulcer effect in a variety of animal models. Ellagic acid was the main responsible for this effect, although other individual ellagitannins could contribute to the biological activity of the mixture. Different preparations of pomegranate, including extracts from peels, flowers, seeds, and juice, show a significant anti-inflammatory activity in the gut. No clinical studies have been found, thus suggesting that future clinical studies are necessary to clarify the beneficial effects of pomegranate in the gastrointestinal tract.